Epidemiology of Patients with Dance-Related Injuries Presenting to Emergency Departments in the United States, 2014-2018. (September 2021) - Honrado, Joshua; Bay, R. Curt; Lam, Kenneth C.
Background: Updated rates and patterns associated with patients with dance-related injuries reporting to US emergency departments (EDs) is needed. Hypothesis: Between the years 2014 and 2018, there will be an observed rise of patients with dance-related injuries seen within US EDs. Study Design: Retrospective analysis. Level of Evidence: Level 4. Methods: Utilizing the National Electronic Injury Surveillance System (NEISS) database, data were abstracted for all structured dance-related injuries for all people who presented to a NEISS participating hospital from January 1, 2014, to December 31, 2018. Data were abstracted on age, sex, race, disposition, location on the body where the injury happened, and free text box regarding the mechanism and nature of the injury. Each patient case was associated with a weight to provide national incidence rate (per 100, 000) estimates. Descriptive statistics were used to summarize counts, percentages, and rates across patient cases. Results: Between years 2014 and 2018, 4152 patients reported to the NEISS EDs with a dance-related injury. Most injuries occurred in female patients (83.3%; n = 3459) and among those who were 10 to 18 years old (76.2%; n = 3164). The most common injuries were ankle sprain/strain (12.7%; n = 527) and knee sprain/strain (10.4%; n = 431). Almost all patients were treated and released (97.1%; n = 4033). These data yielded population-weighted estimates of 125, 618 injuries for the study period, with an increasing trend over time (19.2% increase over 5 years). Incidence rates were over 4 times higher for female (12.4) than for male patients (3.0) and highest in the 10- to 18-year-old age group (incidence rate = 46.4). Conclusion: Patients with dance-related injuries reporting to EDs increased over a 5-year period from 2014 to 2018. The majority of dancers in the study were female patients, between the ages of 10 and 18 years, nearly half of the patients reported to the ED with a sprain/strain, and almost all patients were treated and released. Clinical Relevance: An increase in access to proper injury prevention medical services and education should be provided to female dancers between the ages of 10 and 18 years. Strength of Recommendation Taxonomy: B.